Polymer and graphene layer to increase dye regeneration and suppress back electron transfer in dye sensitized solar cells - Sudhakar, Vediappan; Arulkashmir, Arulraj; Krishnamoorthy, Kothandam (Chemical Communications, 2017)
Dye regeneration was improved by using an optimum quantity of graphene, which was dispersed in a polymer that suppresses back electron transfer. Using this approach, DSSCs with an efficiency of 10.4% have been fabricated.